2017
DOI: 10.1042/bsr20170186
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of microRNA-135b-5p protects against myocardial ischemia/reperfusion injury by activating JAK2/STAT3 signaling pathway in mice during sevoflurane anesthesia

Abstract: The study aims to explore the effects of miR-135b-5p on myocardial ischemia/reperfusion (I/R) injuries by regulating Janus protein tyrosine kinase 2 (JAK2)/signal transducer and activator of transcription (STAT) signaling pathway by mediating inhalation anesthesia with sevoflurane. A sum of 120 healthy Wistar male mice was assigned into six groups. Left ventricular ejection fraction (LVEF) and left ventricular shortening fraction (LVSF) were detected. Cardiomyocyte apoptosis was determined by terminal dexynucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…1,2 Studies identified various molecular and cellular mechanisms involved in the process of myocardial I/R. [3][4][5][6][7] Of these, intracellular calcium [Ca 2+ ]i overload is a critical one that leads to cardiomyocyte apoptosis and cell death. [8][9][10] Dexmedetomidine (DEX) is a highly selective α2-adrenoceptor agonist with sedative, anxiolytic, analgesic, and sympatholytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Studies identified various molecular and cellular mechanisms involved in the process of myocardial I/R. [3][4][5][6][7] Of these, intracellular calcium [Ca 2+ ]i overload is a critical one that leads to cardiomyocyte apoptosis and cell death. [8][9][10] Dexmedetomidine (DEX) is a highly selective α2-adrenoceptor agonist with sedative, anxiolytic, analgesic, and sympatholytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al also verified that miR-135b inhibition caused an increase in the expression of JAK2, resulting in the activation of JAK2/STAT3 and protecting the myocardial cells from the ischemia-reperfusion injury. 35 Increasing evidence has shown that JAK2 activation would give rise to the interactive phosphorylation of the residues of tyrosine, and the resultant p-JAK2 provided the anchor sites for the downstream STAT3. Under the phosphorylation, STAT3 would be activated and transferred into the nucleus to regulate the gene transcription and protein expression; here, JAK2/STAT3 signaling pathway was fully activated.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA induces cleavage or blockage of translation of the target mRNAs by complete or incomplete complementary binding to the 3′ untranslated region (UTR) of mRNAs. The role of abnormal expression and function in myocardial [12], spinal cord [13], and renal [14] I-R injury has attracted increasing attention. Studies have shown that miR-15b plays a role in the I-R injury of cardiomyocytes [15,16] and nerve cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that apigenin is closely related to JAK2-STAT3 pathway activity and ischemia-reperfusion injury [22]. The activity of the JAK2-STAT3 pathway is closely related to injury to the heart [8,10,12], kidneys [7,9], and brain [11]. Luo found that osthole reduced renal reperfusion injury by regulating JAK2-STAT3 pathway activity [7].…”
Section: Introductionmentioning
confidence: 99%